Brain-derived neurotrophic factor in hematological malignancies: From detrimental to potentially beneficial. (January 2022) - Azoulay, David; Horowitz, Netanel A.
Abstract: Emerging studies have highlighted brain-derived neurotrophic factor (BDNF), a neuronal growth factor abundant in the peripheral blood, and its tyrosine kinase receptor TRKB, as onco-genes and proteins that support the survival of malignant hematological cells. In contrast, other researchers reported on a favorable association between BDNF blood levels and prognosis, chemotherapy response and neurological side effects in patients with hematological malignancies. Here, we review the accumulated data regarding the expression of BDNF and its receptors in normal hematopoietic and lymphatic cells and tissue. In addition, in-vitro experiments, animal models and human sample studies that investigated the role of BDNF and its receptors in hematological malignancies are discussed. Finally, directions for future research aimed at revealing the mechanisms underlying the protective effect of BDNF in patients with these diseases are suggested.